2021
DOI: 10.1186/s12934-021-01684-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive quantification of anaerobic gut fungi and methanogens in co-culture reveals increased fungal growth rate and changes in metabolic flux relative to mono-culture

Abstract: Background Quantification of individual species in microbial co-cultures and consortia is critical to understanding and designing communities with prescribed functions. However, it is difficult to physically separate species or measure species-specific attributes in most multi-species systems. Anaerobic gut fungi (AGF) (Neocallimastigomycetes) are native to the rumen of large herbivores, where they exist as minority members among a wealth of prokaryotes. AGF have significant biotechnological po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…3C ). While non-rhizoidal strains such as C. churrovis are well-suited for cultivation conditions that allow the concentrations of anaerobic fungi to be measured and subsequent flux calculations to be performed (Leggieri et al., 2021 ), the current study suggests a potential trade-off to using non-rhizoid-forming fungi to liberate sugar from lignocellulose, which ultimately limits its ability to generate nutrients for a co-cultured partner like C. acetobutylicum . Gas pressure readings also showed that addition of C. acetobutylicum to reed canary grass in the absence of fungi led to negligible growth, as this bacterium does not possess CAZymes to hydrolyze lignocellulose (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…3C ). While non-rhizoidal strains such as C. churrovis are well-suited for cultivation conditions that allow the concentrations of anaerobic fungi to be measured and subsequent flux calculations to be performed (Leggieri et al., 2021 ), the current study suggests a potential trade-off to using non-rhizoid-forming fungi to liberate sugar from lignocellulose, which ultimately limits its ability to generate nutrients for a co-cultured partner like C. acetobutylicum . Gas pressure readings also showed that addition of C. acetobutylicum to reed canary grass in the absence of fungi led to negligible growth, as this bacterium does not possess CAZymes to hydrolyze lignocellulose (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Differences in overall architecture, size, and residence time in alimentary tracts of different hosts could result in niche-driven selection of distinct AGF communities. In addition, variation in bacterial and archaeal community structures between hosts could also elicit various levels of synergistic, antagonistic, or mutualistic relationships that impact the AGF community 78 81 . However, domestication status could counter, modulate, or override host identity.…”
Section: Discussionmentioning
confidence: 99%
“…The breakdown of glucose into acetate produces more ATP than lactate because the acetate conversion process reduces pyridine nucleotides and produces ATP (Marvin-Sikkema et al 1990;Wilken et al 2021). Graaf et al (2011) and Leggieri et al (2021) showed that pyruvate converted to Acetyl CoA first and finally converted to acetate. Every transformation of Acetyl CoA to acetate by ASCT (Acetate: Succinyl CoA Transferase) and SCS (Succinate CoA Synthase) enzyme in hydrogenosomes produce ATP (Graaf et al 2011;Makiuchi and Nozaki 2014;Gawryluk et al 2016).…”
Section: The Proportion Of Partial Vfamentioning
confidence: 99%